Acehnese’s Attitude in Using Vernacular through Hadih Maja in Banda Aceh - Erwina Gusti; Siti Aisah Ginting (LINGUISTIK TERAPAN, 2016)
This study explains Acehnese’s Attitude in using vernacular through Hadih Maja in Banda Aceh.  The objectives of this study are (1) to describe the kinds of language attitude used by adolescents in using vernacular in Banda Aceh;  (2)  to investigate the behavior of the adolescents when they are using their vernacular; (3) to explain the process of the adolescents use the conserved Hadih Maja as representative in using their vernacular. This qualitative research selected 30 Acehnese adolescents who lived in Banda Aceh taken by purposive random sampling. Questionnairre was used to collect the data of Acehnese adolescents’ language attitude towards their vernacular. Interview was used to collect the data of the adolescents’ reasons in using their vernacular. Transcription of Acehnese adolescents’ conversation from audio recorder was used to get the data of the attitude by Acehnese adolescents. The data were analyzed by using interactive model by Moeleong. This research found that: (1) the adolescents used negative attitude in using vernacular in Banda Aceh; (2) they showed negative attitude in using vernacular because irresponsibility toward vernacular based on the philosophy of Hadih Maja; (3) and they used Hadih Maja in certain situation namely, wedding ceremony and traditional art program because their awareness to conserve it as their representative in using their vernacular. Keywords: language attitude, Acehnese vernacular, Hadih Maja